Crystals of organic semiconductors via solution growth - Zhou, Jinbo. (2009)
Some organic single crystals are very promising materials for electronic and optoelectronic industry. But since they are generally insoluble in common solvents, they are mostly grown by vapor transportation which is relatively complex and costly. In this report, single crystals are grown out for four typical organic materials via simple solution growth technique. Anthracene and 9,10-diphenylanthracene are grown from toluene with temperature rising up to 100°C and slow cooling. Pentacene and tetracene are grown from high boiling point solvents in a vacuum glass tube, with temperature rising up to 190-200°C and slow cooling. The crystals are found to have high purity from FTIR and MALDI analysis. Their morphology quality is comparable or even better than the crystals grown from vapor transportation.